Mercado livre de energia: avanços legislativos e impactos na transição energética brasileira - Coimbra, Gabriela Oliveira (Universidade Federal de São Carlos, 2025)
The free energy market in Brazil has been consolidating as a strategic mechanism to promote competitiveness and sustainability in the energy sector. With regulatory flexibility and incentives for the use of renewable sources, the Free Contracting Environment (ACL) has played a fundamental role in the sector’s modernization. This study analyzes the historical and regulatory evolution of the ACL, highlighting milestones such as Law No. 9.074/1995 and the recent Ordinances 514/2018 and 50/2022, which expanded consumer access to the free market. The research, qualitative and exploratory in nature, is based on a bibliographic review to understand the benefits and challenges of the ACL in the energy transition. Among the main benefits are cost reduction, freedom to choose suppliers, and encouragement of clean energy sources such as solar and wind. However, challenges such as the need for infrastructure investments, access regulation, and the intermittency of renewable sources still pose obstacles to market expansion. The analysis indicates that the full opening of the ACL, as proposed in bills like PL 414/2021, could democratize access to sustainable energy and increase sector competitiveness. However, this transition requires regulatory adjustments, rebalancing of sectoral charges, and measures to ensure security and stability in the electrical system. Finally, the study presents recommendations for strengthening the ACL, including regulatory improvements, consumer training, and incentives for distributed generation, aiming for a more efficient, accessible, and sustainable energy market.
Free energy earket: legislative advances and impacts on the brazilian energy transition
Keywords: Transição energética; Sustentabilidade; Fontes renováveis; Energy transition; Renewable energy; Sustainability; ENGENHARIAS; 7. Energia limpa e acessível